A brief review of the stony coral (Cnidaria: Anthozoa: Scleractinia) papers published by Zootaxa in its first 20 years - Cairns, Stephen D.; Baron-Szabo, Rosemarie C. (Zootaxa, 2021)
In the 20 year history of Zootaxa, thirty-two papers have been published having Scleractinia as its primary focus. Twenty-four of the 32 scleractinian papers deal with Recent taxa, most of which belonging to shallow-water, reef corals. The 8 publications dealing with fossil Scleractinia include 3 monographic works, three papers discussing nomenclatural issues of individual taxa, and 2 papers deal with various aspects of select genera.